IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING THROUGH CONTROVERSY JIGSAW IN THE ELEVENTH GRADE STUDENTS OF MAN 3 KEDIRI - safitri, Lia (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Having been aware of the difficulties foreign language learners’ experience with writing and their achievement in writing class, the researcher decided to do this study whether Controversy Jigsaw can improve students’ achievement of the Eleventh Grade students of MAN 3 Kediri. This study used qualitative design while Classroom Action Research (CAR) as the approach. This study was conducted in the eleventh grade students of Religion Science Program. There were 40 students, 14 male students and 26 female students. To know the result of students’ activity the researcher used observation checklist, filed note, questionnaire, and interview. Meanwhile, to know the improvement of the achievement the researcher used test and observed the result of test by computing the mean and the percentage of classroom success. The result of the study showed that more than 80% students were more active and more interest in writing activity. In the cycle I the mean of students’ value was 78.11 and 71.05% students could achieve the criteria of success. In the cycle II the mean was 81.68 and 86.84% students could achieve the criteria of success. It can be concluded that Controversy Jigsaw is one of Jigsaw variations that can improve students’ achievement in writing.